Les anotacions marginals al «De amore» català - Cantavella, Rosanna (Caplletra. Revista Internacional de Filologia, 2007)
A new, philological edition of the marginal notes in Andreas Capellanus’ «DeAmore’s» medieval Catalan translation, uniquely preserved in Real Biblioteca de Madrid’s manuscript II-3096 (I), accompanied by transcriptions of the sentence or paragraph which each note refers to. These notes are thematically classified in four groups and described so as to outline their medieval annotator’s main interests.